A MODIFIED DAI-YUAN CONJUGATE GRADIENTMETHODS AND ITS GLOBAL CONVERGENCE - Ahmed, Huda; Al-Naemi, Ghada (Iraqi Journal of Science, 2024)
Based on the conjugacy condition often which is satisfy by quasi-Newton method, thenew version of DY nonlinear conjugate gradient method is proposed, which is descentmethods even with inexact line searches. The search direction of the proposed methodhas the form k k k k k d  g  d 1 1 1   . When exact line search is used, the proposedmethod reduce to the standard DY method. Convergence properties of the proposedmethod is discussed. Numerical results are reported.